Evaluation of graphical and multivariate statistical methods for classification and evaluation of groundwater in Alathur block, Perambalur District, India - Ahamed, A. Jafar; Loganathan, Karuppiah; Ananthakrishnan, S; Jalal, K. C. A.; M.A., Ashraf (ALÖKI Applied Ecological Research and Forensic Institute Ltd., 2017)
This paper assesses the quality of water using different graphical and statistical methods like Durov, Schoeller, Piper – Tri linear diagram, Box and Whisker plot for three seasons in the study area Alathur block, Perambalur District. The graphical representation provides limitations compared with the multivariate method for large data sets. A total of 10 groundwater samples were collected from hand dug wells in this area and they were analyzed for various physical and chemical parameters. The sequence of the dominance of the major ions are in the following order Na+> Ca2+> Mg2+> K+and Cl-> SO42-> HCO3-> NO3-. The dominating hydrochemicals of facies of groundwater are Ca-Cl and mixed Ca-Mg-Cl and alkaline earth metals (Ca2+, Mg2+) and strong acids (SO42-, Cl-) that dominate over alkalis (Na+, K+) and weak acids like HCO3-, CO3-. Based on the analytical result, groundwater in the study area is generally hard to very hard, slightly alkaline to brackish in nature. This indicates that leaching of salts, rock weathering and evaporation are among the most dominant processes in controlling water quality. For industrial purposes, the quality of water was assessed by using the Langeliner saturation index (LSI) and Ryznar saturation index (RSI). Seasonal variations in different parameters were also determined.